Analysis of Household Expenditure on Electricity in Palestine - Jawad, Yousef Abdel; Ayyash, Issam (International Journal of Energy Economics and Policy, 2019)
The aim of the study is to explore and determine the factors influencing household expenditure on electricity in Palestine for 2011, using the OLS method in data analysis, and using the logarithmic model. The effect of the number of dwelling rooms, number of bedrooms, income, number of family members, and goods and services on household electricity expenditure. The study found that the number of rooms in the dwelling, number of bedrooms, income, number of family members, total expenditure on goods and services were all statistically significant and positively associated with spending on electricity. The study showed that the urban areas are the most spending on electricity, and according to the region, the study showed that the central areas of the West Bank is the most spending on electricity, while it was found that the housing used in the construction of external walls concrete, the least expenditure on electricity. Keywords: Household electricity, Expenditure on electricity, Electricity in Palestine. JEL Classifications: B22, C21, C51, Q43, P21 DOI: https://doi.org/10.32479/ijeep.8035